The role of immunotherapy in non-clear cell renal cell carcinoma - Climent, Carla; Soriano, Sandra; Bonfill, Teresa; Lopez, Natalia; Rodriguez, Marta; Sierra, Marina; Andreu, Pablo; Fragio, Monica; Busquets, Mireia; Carrasco, Alicia; Cano, Ona; Seguı́, Miguel-Angel; et al. (Frontiers in Oncology, 2023)
The category of non-clear cell renal cell carcinoma (nccRCC) includes several clinically, histologically, and molecularly diverse entities. Traditionally, they comprise type 1 and type 2 papillary, chromophobe, unclassified and other (medullary, collecting duct carcinoma, translocation-association). Molecular knowledge has allowed us to identify some other specific subtypes, such as fumarate hydratase-deficient renal cell carcinoma (RCC) or succinate dehydrogenase-associated RCC. Additionally, it has permitted us to recognize some alterations with a possible predictive role, as an example we found MET alterations in papillary tumors. The standard therapies incorporated into the management of advanced clear cell renal cell carcinoma (ccRCC), both vascular endothelial growing factor receptor (VEGFR) pathway inhibitors and mTOR inhibitors have shown poorer results in nccRCC patients. There is still an unmet need to improve the efficacy in the treatment of advanced nccRCC. Immunotherapy, especially immune checkpoints inhibitors (ICI) targeting PD-1/PD-L1 and CTLA4, have demonstrated a significant survival benefit in several malignant neoplasias, including ccRCC, with a proportion of patients achieving long survival. Combinations of ICI or ICI plus VEGFR tyrosine kinase inhibitors (TKI) are the standard of care in advanced ccRCC. Unfortunately, pivotal trials did not include any specific nccRCC population. Several studies have retrospectively or prospectively evaluated ICI alone or in combination with another ICI or with TKI in nccRCC patients. In this article, we review data from available trials and try to elucidate clinical and molecular profiles that could benefit from immunotherapy approaches.